Large Ring Cyclodextrin and Cosolvency-based Techniques to Improve Solubility of Antifungal Drug - Gohil, Dr. Dipti (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: Posaconazole is used to treat oral candidiasis in patients who are severely immunocompromised. Posaconazole is categorized under BCS Class-Ⅱ drug, i.e., low solubility and high permeability. Posaconazole has very poor water solubility. The current study aimed to improve water solubility of posaconazole using different approaches. Materials and Methods: To enhance the solubility of drug, two methods, inclusion complex and cosolvency approach, were performed. In inclusion complex method, beta-cyclodextrin (β-CD) and hydroxypropyl β-CD (HP-β-CD) were used for the preparation of inclusion complex. In cosolvency method, two different solvents polyethylene glycol-400 (PEG-400) and propylene glycol (PG) were used. Results: The inclusion complex of HP-β-CD was prepared by physical mixing, kneading, and solvent evaporation methods by taking 1:0.5, 1:1, and 1:2 molar ratio of Drug: HP-β-CD. From the results of dissolution study of complex, it was observed that there was no significant improvement in solubility of drug. In cosolvency approach, maximum solubility of drug was found in a ratio of 0:100% v/v for both solvents. The solubility of drug in Water: PEG- 400 and Water: PG solvents were found to be 20.228 ± 0.0169 mg/mL and 17.204 ± 0.0178 mg/mL, respectively. Conclusion: In cosolvency method, it was observed that drug has more solubility in PEG- 400 compared to PG. Hence, PEG-400 solvent was selected for drug solubilization.